Dampak Peggunaan Media Sosial Terhadap Kesehatan Mental Dan Kesejahteraan Sosial Remaja Dimasa Pandemi Covid-19 - Septiana, Nila Zaimatus (Universitas Nusantara PGRI Kediri, 2021)
During a pandemic the number of social media use for children and adolescents is increasing, and this increase has both positive and negative impacts. This study aims to find the influence of social media use on mental health and social welfare for adolescents during the Covid-19 pandemic. Respondents of this study were 257 people aged around 12 to 19 years. This study uses a quantitative approach with an explanatory design. Data analysis in this study used simple linear regression analysis and MANOVA analysis. The results of the study show that there is an influence between the use of social media on mental health and social welfare of adolescents during the Covid-19 pandemic.